Application of image‐guided navigation system for laparoscopic hepatobiliary surgery. Issue 1 (3rd April 2019) - Yasuda, Jungo; Okamoto, Tomoyoshi; Onda, Shinji; Fujioka, Shuuichi; Yanaga, Katsuhiko; Suzuki, Naoki; Hattori, Asaki
Abstract : Background: To achieve safety of the operation, preoperative simulation became a routine practice for hepatobiliary and pancreatic (HBP) surgery. The use of intraoperative ultrasonography (IOUS) is essential in HBP surgery. There is a limitation in the use of IOUS in laparoscopic surgery (LS), for which a new intraoperative system is expected. We have developed an image‐guided navigation system (IG‐NS) for open HBP surgery since 2006, and we have applied our system to LS. The aim of this study is to evaluate the results of clinical application of IG‐NS in LS. Materials and methods: Eight patients underwent LS using IG‐NS; LS consisted of cholecystectomy and hepatectomy in four patients each. After registration, the 3D models were superimposed on the surgical field. We performed LS while observing the navigation image. Moreover, we developed a support system for operations. Results: The average registration error was 8.8 mm for LS. Repeated registration was effective for organ deformation and improved the precision of IG‐NS. By using various countermeasures, identification of the tumor's position and the setting of the resection line became easy. Conclusion: As IG‐NS provided real‐time detailed and intuitive information, this intraoperative assist system may be an effective tool in LS.